2012
DOI: 10.1177/1098612x12463928
|View full text |Cite
|
Sign up to set email alerts
|

Serum thymidine kinase activity in clinically healthy and diseased cats: a potential biomarker for lymphoma

Abstract: The thymidine kinases are enzymes that convert deoxythymidine to deoxythymidine monophosphate and have a function in DNA synthesis. Rapidly proliferating cells will have higher levels of thymidine kinase. Serum thymidine kinase activity (sTK) is a useful tumour marker in humans and dogs, with utility as a prognostic indicator in lymphoma. In the current study serum samples were collected from 49 clinically healthy cats, 33 with lymphoma, 55 with inflammatory disease and 34 with non-haematopoietic neoplasia (NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Using disease indicators from feces, 6 it was previously shown that fecal α1-PI concentration is higher in cats with severe IBD or ALA. The same study showed that low serum albumin and total protein concentrations may be common findings in cats with IBD or ALA. Serum thymidine kinase activity 31 has been reported to be a useful tumor marker in humans and animals. The level of thymidine kinase in serum has shown also to be a prognostic indicator of ALA.…”
Section: Discussionmentioning
confidence: 99%
“…Using disease indicators from feces, 6 it was previously shown that fecal α1-PI concentration is higher in cats with severe IBD or ALA. The same study showed that low serum albumin and total protein concentrations may be common findings in cats with IBD or ALA. Serum thymidine kinase activity 31 has been reported to be a useful tumor marker in humans and animals. The level of thymidine kinase in serum has shown also to be a prognostic indicator of ALA.…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum TK1 activity is seen associated with leakage of the enzyme from dying cells during replication and increased activity of TK1 is associated with hematologic neoplasia in humans 5,6 . Serum TK1 activity is used as a marker of lymphoma in dogs and cats 4,7,8 . The use of TK1 has expanded in other species, including monitoring progression of disease and remission in dogs, cats, and humans 9‐12 .…”
Section: Introductionmentioning
confidence: 99%
“…2,4,5 In veterinary species, high levels of serum TK1 compared with normal range are detected in canine lymphoma, splenic hemangiosarcoma, and feline lymphoma. [2][3][4][5][6][7][8] Solid tumors in dogs and humans do not show consistently increased levels precluding serum TK1 levels as a general biomarker for all cancer histologies. 3 However, it is used in humans for breast, lung, and colorectal cancer.…”
Section: Tests For Lymphoma Veterinary Diagnostics Institute Tkcanine1mentioning
confidence: 95%